Credit Risk in Islamic Banks of GCC Countries - Al-Wesabi, Hamid Abdulkhaleq Hasan (2012)
This study investigates factors which affect credit risk of Islamic banks in Gulf Cooperation Council (GCC) countries. The study uses secondary data obtained from the web sites of 25 Islamic banks during the period from 2006 to 2010. We exclude Saltant Oman which has no Islamic banks. This study uses Non-Performing loans (NPLs) as a proxy for credit risk which is dependent variable. The independent variables consist of three macroeconomic variables Gross Domestic Product (GDP), Inflation rate (INF) and London Inter-Bank Offered Rate and six other variables (bank specific) that are used as internal variables. These are management efficiency (MGTEFF), loan to deposit (L/D), risky asset (RSKAST), total assets (LNTA), regulatory capital (REGCAP) and loan loss provision (LLP). We find that GDP is significant and negatively related to credit risk, and it is similar with finding of past studies, but inflation rate and LIBOR are insignificantly related, and they are different with literature. We find that MGTEFF is significantly and negatively related to credit risk, while L/D and RSKAST are significant and positively related to credit risk. All of them are similar with finding of previous studies. And other internal variables (LNTA, REGCAP, and LLP) are not significantly related to the credit risk. Size of banks is differed with past studies, LNTA and REGCAP are positive related to credit risk, while LLP is negative related to the credit risk of Islamic banks in GCC countries.